2021
DOI: 10.3390/d13060271
|View full text |Cite
|
Sign up to set email alerts
|

Postojna-Planina Cave System in Slovenia, a Hotspot of Subterranean Biodiversity and a Cradle of Speleobiology

Abstract: The Postojna-Planina Cave System (PPCS) in central Slovenia is a globally exceptional site of subterranean biodiversity, comprised of many interconnected caves with cumulative passage length exceeding 34 km. Two rivers sink into the caves of the PPCS, called the Pivka and Rak, and join underground into Unica River, which emerges to the surface. The studies of fauna of PPCS began in the 19th century with the first scientific descriptions of specialized cave animals in the world, making it “the cradle of speleob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…2b). The most studied show cave is Postojna cave in Slovenia, which is also recognized as the most important global subterranean biodiversity hotspot (Zagmajster et al 2021), followed by two Spanish show caves, i.e. Nerja Cave and Castañar de Ibor Cave, and by Lascaux Cave in France (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2b). The most studied show cave is Postojna cave in Slovenia, which is also recognized as the most important global subterranean biodiversity hotspot (Zagmajster et al 2021), followed by two Spanish show caves, i.e. Nerja Cave and Castañar de Ibor Cave, and by Lascaux Cave in France (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Planinska jama is one of the underground habitats with high biodiversity, including the olm Proteus anguinus Laurenti, 1768, endemic species of amphipod Niphargus Schioedte, 1849, isopods Monolistra Gerstaecker, 1856, Asellus aquaticus cavernicolus Racovitza, 1925 andTitanethes albus (C. Koch, 1841), cave shrimp Troglocaris planinensis Birstein, 1948, cave hydrozoan Velkovrhia enigmatica Matjašič & Sket, 1971, and eight (Culver & Sket, 2000 mostly stygophile gastropod species (including terrestrial Zospeum Bourguignat, 1856 and pulmonate aquatic Ancylus fluviatilis O. F. Müller, 1774), whose empty, two to three millimeter-sized shells form dune-like thanatocenoses at some places. According to Sket (1999) in the Planinska jama PPCS 19, and according to Zagmajster et al (2021) nine (in this seven Truncatelloid) aquatic gastropod species were found, and the number of troglobiotic and stygobiotic animal species approaches 120, similarly high number can be found only in Vjetrenica Cave in Bosnia and Herzegovina . Also the material from earlier studies, collected at 14 other localities in Slovenia, Croatia, and Bosnia and Herzegovina (Table 1, Fig.…”
Section: Methodsmentioning
confidence: 93%
“…One potential problem is that even though cave communities are indeed simpler than surface communities in the typical A. aquaticus habitats, some of the studied caves can be considered harboring diverse communities by subterranean standards. For example, the Postojna-Planina Cave System harbors 50+ aquatic species including predators, and can be considered as a hotspot for subterranean biodiversity (Zagmajster et al, 2021). The Movile Cave, which is one window of access to the Movile aquifer, harbors 20+ aquatic species, also including aquatic predators (Brad et al, 2021).…”
Section: Figurementioning
confidence: 99%